2020
DOI: 10.1177/0748730419900868
|View full text |Cite
|
Sign up to set email alerts
|

CikA, an Input Pathway Component, Senses the Oxidized Quinone Signal to Generate Phase Delays in the Cyanobacterial Circadian Clock

Abstract: The circadian clock is a timekeeping system in most organisms that keeps track of the time of day. The rhythm generated by the circadian oscillator must be constantly synchronized with the environmental day/night cycle to make the timekeeping system truly advantageous. In the cyanobacterial circadian clock, quinone is a biological signaling molecule used for entraining and fine-tuning the oscillator, a process in which the external signals are transduced into biological metabolites that adjust the phase of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
(56 reference statements)
3
14
0
Order By: Relevance
“…CikA’s name ( c ircadian i nput k inase) implies its important role in transmitting environmental signals to the clock. More recent work found that including CikA in the IVO reaction can enable delays in the KaiC phosphorylation peak when quinone is added at certain circadian times (CTs), while only phase advances were observed without CikA, consistent with a role in input ( 38 ). CikA and SasA both act in output pathways where they regulate the activity of the transcription factor, and additionally affect the period of the core oscillator and have features of oscillator components ( 23 , 33 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…CikA’s name ( c ircadian i nput k inase) implies its important role in transmitting environmental signals to the clock. More recent work found that including CikA in the IVO reaction can enable delays in the KaiC phosphorylation peak when quinone is added at certain circadian times (CTs), while only phase advances were observed without CikA, consistent with a role in input ( 38 ). CikA and SasA both act in output pathways where they regulate the activity of the transcription factor, and additionally affect the period of the core oscillator and have features of oscillator components ( 23 , 33 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we proposed that a KaiC-alone hourglass can oscillate under the alternating Mg 2+ concentrations in vitro, and that this perhaps put the emergence of Mg 2+ homeostasis after that of the primeval timekeeper on the clock’s evolutionary timeline [ 14 ]. Since the endogenous Mg 2+ concentration was reported to be constant in S. elongatus [ 43 ], the emergence of a damped oscillator as a better timekeeping system than the cue-dependent hourglass fits well in the picture [ 39 ]. After going through multiple evolutionary steps, the current self-sustained circadian oscillator may have emerged as a biologically efficient way to exploit the periodic availability of solar energy.…”
Section: Discussionmentioning
confidence: 99%
“…KaiB binding‘s allosteric induction of A-loop burial also had a potential role in the entrainment process since maintaining the A-loop’s buried conformation during the falling phase of the clock was crucial not only for maintaining the KaiC–KaiB–CikA complex, but also because KaiA could not tether the A-loop in its exposed conformation and run the rhythm backward toward phosphorylation. If the A-loop became exposed at this stage, KaiA, not CikA, would have been inactivated by oxidized quinone, which would have advanced the phase instead of delaying it [ 43 , 45 , 46 ]. It is through this process that KaiB initiated the dephosphorylation phase at the correct timing of day and ensured that the CikA binding took place accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…CikA also has a PsR domain, which resembles that of KaiA [ 45 ], and oxidized quinone inactivates CikA in a similar manner. Therefore, now CikA and oxidized quinone are added into the standard KaiABC in vitro mixture in order to test whether CikA contributes to a phase delay in response to quinone [ 46 ]. During KaiC’s nighttime dephosphorylation phase, KaiA and CikA compete for the same binding site on KaiB.…”
Section: Entrainment Through the Input Pathwaymentioning
confidence: 99%
“…Previously, the standard KaiABC oscillator mixture has been shown to be relatively immune in the biologically meaningful range of temperature between 25 °C and 35 °C, with a Q 10 value close to 1.0 [ 13 ]. In a similar manner, quinone entrainment with the addition of CikA into the mixture also turned out to compensate for temperature [ 46 ].…”
Section: Entrainment Through the Input Pathwaymentioning
confidence: 99%